Contrasting the drivers of customer loyalty; financing and depositor customer, single and dual customer, in Indonesian Islamic bank. Issue 4 (5th August 2019) - Kartika, Tika; Firdaus, Achmad; Najib, Mukhamad
Abstract : Purpose: This study aims to investigate the drivers of loyalty in Indonesian Islamic banks, especially group of depositor vs financing customer and single vs dual customer. Design/methodology/approach: The objectives of this study were the seven major commercial Indonesian Islamic banks using the purposive sampling technique. In total, 105 questionnaires were processed, consisting of questions regarding depositors, financing, single and dual customer. Structural equation modeling using partial least squares were the analysis methods used to test the hypothesis, while in-depth interviews were conducted with Islamic bank managers to validate the findings. Findings: Image has a significant relationship with customer satisfaction, as well as trust. Similarly, customer satisfaction has a significant relationship with trust. Trust has a significant relationship with loyalty. For a financing customer, the image is very influential on customer trust. For a depositor customer, customer satisfaction is very influential on customer trust. For single customer, customer satisfaction has a stronger influence on the image, compared to dual customer. Practical implications: Islamic banks need to maintain good image and service quality to create strong, reliable and long-term relationships with customers, more specifically, in terms of improvement and product innovation. A bank focuses on the micro or macro segment, as well as financing. Financing products should be referred to customers' needs. Bank reputation can be done by strengthening branding and corporate culture in marketing strategy. Shariah compliance has the highest loading factor to trust customers. Indonesian Islamic banks need to maintain customer trust by sticking to Islamic principles and continuing to ensure that its products and services are in accordance with Islamic principles. In Indonesian Islamic banks, it is very important to keep the legal aspects in all of products and services. Deposit products and services of Islamic banks should be in line with the rules of the financial services authority and Bank of Indonesia culture. Bank efforts to strengthen reputation can be done by strengthening branding and corporate culture in marketing strategy, while increasing the attractiveness of the products by way of research and development (R&D) must endeavor to make products and services attractive in terms of both product characteristics and price. Furthermore, it is necessary to support a good marketing strategy to market their products. Social implications: Research can be used more widely in determining public policy, by strengthening the marketing strategy and public education. Islamic banks can work together with local religious departments to maximize marketing strategies to educate and convince people to be active economically under Islamic sharia guidance. Islamic banks need to maintain customer trust by sticking to the principles of sharia and continuing to ensure that products and services conform to sharia principles. Islamic bank management can strengthen customer trust by having a good risk management system, so that customers feel secure with Islamic bank transactions. In addition, sharia banks as companies must demonstrate social responsibility by distributing ZIS managed from customers and implementing CSR as a form of awareness of the surrounding community. Originality/value: The study revealed the factors that lead to loyalty on the financing, depositor and the single and dual customers. The study found that improvement and innovation, strategic and sustainability are new indicators used to build images of Islamic banks.